A review of single aerosol particle studies in the atmosphere of East Asia: morphology, mixing state, source, and heterogeneous reactions. (20th January 2016) - Li, Weijun; Shao, Longyi; Zhang, Daizhou; Ro, Chul-Un; Hu, Min; Bi, Xinhui; Geng, Hong; Matsuki, Atsushi; Niu, Hongya; Chen, Jianmin
Abstract: Emissions of anthropogenic air pollutants in East Asia significantly influence the regional climate, cause environmental deterioration and threaten public health. Single particle analyses have been widely applied to study aerosol particles collected on the ground and at elevated altitudes at mountains and by flights. Here we review current understanding on physicochemical properties, mixing state, heterogeneous chemical reactivity of individual particles in East Asia based on electron microscopy and mass spectrometry. We summarize the techniques of single particle analysis and discuss their advantages and disadvantages. Morphology and composition of the major particle types in East Asia obtained by these techniques are briefly introduced and are further used to identify particle sources. The diversity, heterogeneity, and variable size of ambient particles make it challenging to understand how the precise single particle analyses are efficient in studying particle optical properties, hygroscopic behavior, related heterogeneous reactions and potential health evaluations. We highlight the combinations of laboratory and field studies, single and bulk analytical methods, and the integration of different single particle technologies that may be very powerful to obtain a more complete picture of single particles. These research results can improve our knowledge on the fundamental physical chemistry of aerosol particles and be further extended to study their environment and climate effects as well as health risk. Highlights: Single particle analyses have been widely applied to study aerosol particles in East Asia. We summarize the techniques of single particle analysis and discuss their advantages and disadvantages. The precise single particle analyses are efficient in studying particle optical properties, hygroscopic behavior, related heterogeneous reactions and potential health evaluations. We highlight the combinations of laboratory and field studies and the integration of different single particle technologies.